The antinociceptive effects of folic acid using formalin and acetic acid tests in male mice - Morteza Hajiallilo; Saeid Abbasi-Maleki (Journal of Shahrekord University of Medical Sciences, 2021)
Background and aims: Antidepressant agents such as imipramine are clinically used to control and treat different types of pain, especially neuropathic pain. Studies have shown the antidepressant-like activity of folic acid (FA). This study aimed to investigate the potential antinociceptive effects of FA using formalin and acetic acid tests in male mice. Methods: Sixty male albino mice (20-30 g) were randomly divided into 10 groups (n=6 in each group) of negative control, positive control (morphine or indomethacin), and FA (10, 15, and 30 mg/kg) groups. In the formalin test, duration of paw licking and biting the right hind paw during acute (0-5 minutes) and chronic (15-60 minutes) pain after intraplantar injection of formalin 2.5% (25 µL) was recorded. In the writhing test, the abdominal constrictions were recorded after the intraperitoneal injection of acetic acid 1%. Results: Only a high dose (30 mg/kg) of FA significantly reduced acute pain (P=0.001) compared with the control group. But all doses of FA significantly decreased chronic pain (P=0.001). In addition, morphine significantly reduced both phases of pain (P=0.020 and P=0.001, respectively). Moreover, indomethacin and all doses of FA decreased the number of abdominal constrictions induced by acetic acid (P=0.001). Conclusion: Compared with acute (neurogenic) pain, FA more potently decreases chronic (inflammatory) pain. Furthermore, FA decreases the parietal pain that could potentially represent antinociceptive effect. However, further studies are needed to elucidate the exact mechanism of FA’s analgesic activity.